2017
DOI: 10.3389/fmars.2017.00246
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of Spatio-Temporal Patterns of Major Mediterranean Phytoplankton Groups from Remote Sensing OC-CCI Data

Abstract: During the last two decades, several satellite algorithms have been proposed to retrieve information about phytoplankton groups using ocean color data. One of these algorithms, the so-called PHYSAT-Med, was developed specifically for the Mediterranean Sea due to the optical peculiarities of this basin. The method allows the detection from ocean color images of the dominant Mediterranean phytoplankton groups, namely nanoeukaryotes, Prochlorococcus, Synechococcus, diatoms, coccolithophorids, and Phaeocystis-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 97 publications
(181 reference statements)
5
19
0
Order By: Relevance
“…The spatiotemporal variability of the dominant PFTs in the Mediterranean Sea observed in this study highlights the dominance of Hapto and Chloro in winter-spring seasons essentially in the western basin, whereas Synechococcus dominate most of the Mediterranean waters during summer. These results agree with previous studies on the Mediterranean Sea (e.g., Navarro et al, 2017;Sammartino et al, 2015;Uitz et al, 2012;Vidussi et al, 2000Vidussi et al, , 2001.…”
Section: Phytoplankton Dynamic In the Mediterranean Seasupporting
confidence: 93%
See 3 more Smart Citations
“…The spatiotemporal variability of the dominant PFTs in the Mediterranean Sea observed in this study highlights the dominance of Hapto and Chloro in winter-spring seasons essentially in the western basin, whereas Synechococcus dominate most of the Mediterranean waters during summer. These results agree with previous studies on the Mediterranean Sea (e.g., Navarro et al, 2017;Sammartino et al, 2015;Uitz et al, 2012;Vidussi et al, 2000Vidussi et al, , 2001.…”
Section: Phytoplankton Dynamic In the Mediterranean Seasupporting
confidence: 93%
“…Journal of Geophysical Research: Oceans Navarro et al (2014Navarro et al ( , 2017 developed a regionalized version of PHYSAT (PHYSAT-Med), which is based on the OC-CCI merged ocean color data. Originally, PHYSAT identifies dominant phytoplankton types using normalized reflectance anomalies.…”
Section: 1029/2019jc015131mentioning
confidence: 99%
See 2 more Smart Citations
“…In the Mediterranean Sea, regional ocean color algorithms and products were used to characterize the spatialtemporal variability of PFTs (Di Cicco et al, 2017;Navarro et al, 2014Navarro et al, , 2017Sammartino et al, 2015;Uitz et al, 2012;Volpe et al, 2007). Observation-based analysis showed that small-sized groups, either PIC (Magazzù & Decembrini, 1995) or NNP (Uitz et al, 2012), can dominate the primary production in the Mediterranean Sea, although MIC production can also be relevant in some spring-blooming Mediterranean areas (Uitz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%